PS-093 Analysis of the variation in the platelet counts of patients treated with linezolid. (24th February 2014) - Santaolalla, I; Martin, I; Rubio, B; Mañes, M; Crespo, P; Segura, M
Abstract : Background: Linezolid is an antimicrobial agent to treat infections of Gram-positive pathogens. While effective, linezolid treatment is frequently associated with haematological side effects. This adverse event does not seem to be of abrupt onset and consequently close monitoring for the blood test abnormalities is important. Purpose: To analyse the incidence of thrombocytopenia, to determine the degree of thrombocytopenia and to decide whether the difference between initial values and final platelet values after linezolid (LZ) treatment is significant. Materials and methods: Prospective study in a 2 nd -level hospital, we included all patients treated with LZ, from January 2012 to August 2013, who did not have TCP pre-treatment. Thrombocytopenia was defined as a decrease in the platelet count to <150, 000 cells/mcL (mild: 150, 000–1, 000, 000, moderate: 100, 000–50, 000 and severe: <50, 000). The data collected were: number of patients, sex, age, days of LZ therapy, platelets at the beginning and at the end of LZ treatment. We performed the Kolmogorov-Smirnov test to check whether the data fitted a normal test and U-Mann Whitney to analyse the differences. Results: 167 patients were included (57.5% men) with a mean age of 68 (interquartile range (IQR): 21); Median days of linezolid therapy were 9 (IQR: 7). The incidence of thrombocytopenia incidence was 13.27% (28 cases). TCP was mild in 19 cases (9%), moderate in 8 (3.79%) and severe in 1 (0.47%). 71.5% of patients presented a reduction in the platelet values, and the difference between initial values and final platelet values after linezolid treatment was significant. Conclusions: The incidence of thrombocytopenia observed in our study was similar to that described in the literature (2.4–64.7%). The thrombocytopenia was severe in 1 case. Other factors that could have been causing thrombocytopenia in patients treated with linezolid were not assessed. Pharmaceutical validation must incorporate an assessment of the platelet count, as it may contribute to early identification of thrombocytopenia. No conflict of interest.